Knowledge and attitudes of rural healthcare providers regarding domestic violence against women: a systematic review - Nascimento, Cláudio Tarso de Jesus Santos; Vidigal, Maria Tereza Campos; Oliveira, Vinícius Henrique Ferreira Pereira de; Franco, Raquel Porto Alegre Valente; Vieira, Walbert Andrade; Jesus-Soares, Adriana de; Lima, Rafael Rodrigues; Franco, Ademir; Paranhos, Luiz Renato (São Paulo Medical Journal, 2025)
BACKGROUND: Specific types of violence such as intimate partner sexual violence and intimate partner homicide occur more frequently in rural areas. OBJECTIVE: This study aimed to systematically review the literature on the knowledge and attitudes of rural healthcare providers regarding cases of domestic violence against women. DESIGN AND SETTING: Systematic review developed at Universidade Federal de Uberlândia. METHODS: We conducted an electronic search of six databases, which only included observational studies, regardless of the year, language, or country of publication, except for studies that used secondary data and were exclusively qualitative. Two reviewers performed the selection, data extraction, and risk of bias assessment using a specific Joanna Briggs Institute tool. RESULTS: Six studies met the inclusion criteria. All the studies had a low risk of bias. Approximately 38% of these professionals identified injuries caused by violence in patients. When asked about knowing the correct attitude to take in cases of confirmed violence, between 12% and 64% of rural healthcare providers answered positively; most of them would refer to specialized institutions and promote victim empowerment and counseling. The number of professionals with an educational background in the field ranged from 16% to 98%. CONCLUSIONS: The evident disparity across studies shows that some professionals have suboptimal knowledge and require training to adopt the correct attitude when identifying female victims of domestic violence in clinical practice. SYSTEMATIC REVIEW REGISTRATION: This systematic review was registered in the Open Science Frame work Database under the registration http://doi.org/10.17605/OSF.IO/B7Q6S.